Harnessing Reality Counseling: Boosting Self-Esteem In Former Schizophrenia Patients Facing Psychosocial Adversities - Diana Savitri Hidayati; Mhd. Ricky Darusman; Annisya Muthmainnah Takdir; Dini Fidyanti Devi (Schema: Journal of Psychological Research, 2025)
Schizophrenia is a complex mental disorder shaped by biological, psychological, and social vulnerabilities. This study explores these factors in a subject with paranoid schizophrenia, complicated by a history of methamphetamine abuse, familial discord, and social rejection. Using a single-subject case study approach, including clinical interviews, behavioral observations, standardized assessments (WAIS, PANSS, WHODAS 2.0, and projective tests), and a Reality Therapy intervention based on the WDEP system, the study revealed significant cognitive impairments, avoidant coping patterns, and unmet psychological needs. The intervention fostered emotional regulation, social engagement, and proactive goal setting, demonstrating its effectiveness in addressing maladaptive behaviors. However, familial rejection and societal stigma persisted as barriers to sustained recovery. These findings highlight the importance of holistic approaches addressing the interconnected dimensions of schizophrenia, emphasizing the role of psychoeducation, family reconciliation, and community support in achieving long-term stability.